An analysis of the Documentary “Altan Tulga, Mungun Totgo” - Basanbayar, Buyannemekh (Mongolian Journal of Arts and Culture, 2025)
Abstract: This study focuses on the documentary film “Altan Tulga, Mungun Totgo”, which depicts the traditional wedding rituals of the Zakhchin ethnic group. It examines the film’s role in documenting, preserving, and disseminating intangible cultural heritage through audiovisual media. As a scholarly inquiry, the research argues that documentary cinema functions not merely as a vehicle for conveying information but also as a vital tool for documenting, safeguarding, and revitalizing cultural practices. The analysis demonstrates that the film effectively captures and preserves distinctive ritual knowledge, provides valuable ethnographic data, and contributes to the intergenerational transmission and contemporary relevance of intangible cultural heritage. “Алтан тулга, мөнгөн тотго” баримтат кинонд хийсэн шинжилгээ Хураангуй: Энэхүү судалгаанд захчин угсаатны хуримын зан үйлийг харуулсан “Алтан тулга, мөнгөн тотго” баримтат киног сонгож соёлын биет бус өвийг киногоор баримтжуулж хадгалах, олон нийтэд сурталчлах боломж, ач холбогдлыг шинжиллээ. Баримтат кино нь зөвхөн мэдээлэл дамжуулагч бус, соёлын өвийн бүртгэл, хадгалалтын хэрэгсэл болох боломжтой. Судалгааны үр дүнд уг баримтат кино нь захчины хуримын зан үйлийг баримтжуулан хадгалах, угсаатны зүйн судалгааны эх сурвалж болохын зэрэгцээ соёлын өвийг орчин үеийн нийгэмд өвлүүлэхэд дэмжлэг үзүүлэх боломжтой гэж үзэж байна. Түлхүүр үгс: бэр сонгох, ам сонсгох, зус хадгийн найр, халхаар цайлуулах, хадаг бараалхуулах, хүргэн үзэгдэх